2017
DOI: 10.1002/bjs5.7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of performance in a mandatory postgraduate surgical examination on selection into specialty training

Abstract: BackgroundThe Intercollegiate Membership of the Royal College of Surgeons (MRCS) examination is undertaken by large numbers of trainees in the UK and internationally as a mandatory step within surgical training. Unlike some high‐stakes medical examinations, the MRCS is yet to be validated. A quantitative study was undertaken to assess its predictive validity by investigating the relationship between MRCS (Parts A and B) and national selection interview scores for general and vascular surgery in the UK.MethodsP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…Research to date has found that Part A MRCS performance predicts performance at Part B, and that Part B MRCS performance itself predicts surgical training outcomes. For example, score and number of attempts at Part B MRCS were found to be significant independent predictors of both selection into higher surgical training (HST, year 3 onwards of training) and performance during HST. Similar relationships have been observed between the written papers and clinical exams of the equivalent physician examination in the UK, the Membership of the Royal College of Physicians (MRCP), and for the Medical Licensing Examination® (USMLE®) in the USA.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…Research to date has found that Part A MRCS performance predicts performance at Part B, and that Part B MRCS performance itself predicts surgical training outcomes. For example, score and number of attempts at Part B MRCS were found to be significant independent predictors of both selection into higher surgical training (HST, year 3 onwards of training) and performance during HST. Similar relationships have been observed between the written papers and clinical exams of the equivalent physician examination in the UK, the Membership of the Royal College of Physicians (MRCP), and for the Medical Licensing Examination® (USMLE®) in the USA.…”
Section: Introductionmentioning
confidence: 57%
“…Age at graduation was included, as older doctors (defined in previous studies as age 29 years or more at graduation from medical school) have been found to be more likely to have problems progressing through training in the UK.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Positivist research questions typically focus on testing and confirming a provisional (null) hypothesis. For example, you might want to examine whether early performance predicts later performance, 5 , 6 whether students spend more time preparing web‐based compared with paper‐based portfolios, 7 or how much variance in Mini‐Clinical Evaluation Exercise (Mini‐CEX) ratings is attributable to raters' social judgments 8 . On the other hand, social constructivist research questions tend to be about hypothesis generation — they are open and exploratory, seeking to understand phenomena such as student culture in a medical school, 9 the unintended consequences of a curriculum reform, 10 or how residents learn 11 .…”
Section: Developing An Educational Research Questionmentioning
confidence: 99%